2019
DOI: 10.1371/journal.pbio.3000057
|View full text |Cite
|
Sign up to set email alerts
|

A small proportion of Talin molecules transmit forces at developing muscle attachments in vivo

Abstract: Cells in developing organisms are subjected to particular mechanical forces that shape tissues and instruct cell fate decisions. How these forces are sensed and transmitted at the molecular level is therefore an important question, one that has mainly been investigated in cultured cells in vitro. Here, we elucidate how mechanical forces are transmitted in an intact organism. We studied Drosophila muscle attachment sites, which experience high mechanical forces during development and requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 67 publications
3
67
0
Order By: Relevance
“…Then, flight muscles build up mechanical tension, compact to about 220 µm in length, while their diameter grows to about 2000 µm 2 , and assemble the immature myofibrils at 32 h APF (Lemke et al, 2019;Weitkunat et al, 2014) (Figure 1A,C). After 32 h, flight muscles grow about 2.5 times in length while keeping the same diameter until 48 h APF.…”
Section: Growth Of Drosophila Flight Musclesmentioning
confidence: 99%
“…Then, flight muscles build up mechanical tension, compact to about 220 µm in length, while their diameter grows to about 2000 µm 2 , and assemble the immature myofibrils at 32 h APF (Lemke et al, 2019;Weitkunat et al, 2014) (Figure 1A,C). After 32 h, flight muscles grow about 2.5 times in length while keeping the same diameter until 48 h APF.…”
Section: Growth Of Drosophila Flight Musclesmentioning
confidence: 99%
“…We found that flight muscle mitochondria are in intimate contact with myofibrils and acquire an elongated shape. We have shown in the past that myofibrils are under significant mechanical tension during development and that this tension is required to build linear myofibrils 18,19 . Hence, we hypothesized that myofibril tension creates a pushing force against mitochondria that constrain them into the observed ellipsoid shape.…”
Section: Flight Muscle Mitochondria Morphology Is Ruled By Mechanicalmentioning
confidence: 99%
“…Visualising these complexes is further complicated as any perturbation of the system will result in altered MeshCODE arrangements. However, the technical capabilities to observe protein states and forces acting on proteins in cells are advancing rapidly (Kumar et al, 2016;Ringer et al, 2017;Lemke et al, 2019) and used in conjunction with super-resolution microscopy techniques (Leterrier et al, 2017;Schnitzbauer et al, 2017;Jacquemet et al, 2020), optogenetic techniques (Liu et al, 2012), and the well-established strategies for studying neurotransmission (reviewed in (Kandel et al, 2014)) such conformational changes during memory formation should be detectable. Further, a number of talin-binding compounds have recently been identified (Yang et al, 2017;Bryce et al, 2019) and the effect of such compounds on learning and memory in animal systems might provide opportunities to pharmaceutically modulate these processes.…”
Section: Discussionmentioning
confidence: 99%